Ferroelectric tunnel junctions: current status and future prospect as a universal memory - Sharma, Urvashi; Kumar, Gulshan; Mishra, Sachin; Thomas, Reji (Frontiers in Materials, 2023)
The semiconductor industry is actively looking for an all-encompassing memory solution that incorporates the advantageous aspects of current technology. This features nonvolatility, like that of Flash memory, high scalability, like that of both Dynamic Random Access Memory (DRAM) and Flash, quick operation, like that of Static RAM (SRAM), and durability, like that of both DRAM and SRAM. Ferroelectric thin films, which have electrically switchable bi-stable polarization, are one prospective technology that has the potential to revolutionize memory storage. However, due to difficulties with scalability and dependable industrial manufacturing, Ferro-Electric (FE) memory technology has not been able to effectively compete with DRAM and Flash. Research in this area has accelerated after the recent discovery of resistive switching in ferroelectric tunnel junctions (FTJs). For FTJs to be successful, it is important to overcome some obstacles, such as preserving bi-stability in ferroelectric thin films over the critical thickness. Additionally, the existence of interfacial layers, sometimes known as a "dead layer", between the electrode and the film can affect its characteristics. The article gives an overview of semiconductor memories with an emphasis on emerging technologies having the potential for future applications. It then goes into detail on the benefits of FTJ and its non-destructive reading capacity. The article also discusses the potential uses for FTJs in resistive switching while acknowledging their drawbacks and constraints.